Effects of high-fidelity simulation and e-learning methods on nursing students’ self-efficacy in patient safety: a quasi-experimental study - Kevser Ozata; Leyla Dinc (BMC Nursing)
Abstract Background Patient safety is a critical indicator of healthcare quality. The professional self-efficacy and skills of nursing students regarding patient safety should be developed and assessed throughout their education. This study aimed to evaluate the impact of e-learning and high-fidelity simulation methods on the self-efficacy of nursing students. Methods A comparative quasi-experimental study was conducted with 52 senior nursing students enrolled at a state university in Ankara. Participants completed a pre-test and were randomly assigned to either a high-fidelity simulation group or an e-learning group, with 26 students in each. Both groups were exposed to five standardized case scenarios. The high-fidelity group participated in face-to-face simulations, while the e-learning group engaged in online discussions centered on the same scenarios. Following these sessions, both groups underwent debriefing before undertaking the first post-test. Subsequently, all students undertook a 3-week clinical placement focused on Patient Safety and Quality, followed by a second post-test. Data were collected using a demographic questionnaire, the Health Professionals’ Education in Patient Safety Survey, and the Patient Safety Competency Self-Efficacy Scale. Data analysis involved descriptive statistics for sociodemographic characteristics, independent samples t-tests and Mann-Whitney U tests for between-group comparisons, and analysis of variance and Friedman test for within-group comparisons. Results The e-learning and high-fidelity simulation interventions both resulted in statistically significant improvements in students’ scores on the Patient Safety Competency Self-Efficacy Scale and its subscales, as well as the Health Professionals’ Education in Patient Safety Survey. However, no significant difference was observed between the two groups. Conclusion Both high-fidelity simulation and e-learning methods focusing on patient safety were equally effective in improving nursing students’ self-efficacy. These results suggest that either method or a combination of both, using case scenarios that reflect real clinical situations, can be effectively employed to improve students’ self-efficacy in patient safety. Clinical trial number Not applicable.